The emerging role of S100A4 and S100A14 proteins in colorectal cancer progression: Role of S100A4 in colorectal cancer - Rasool, Shelan; Hussein, Zihel; Ali, Hazhmat; Al Ismaeel, Qais; AL-Mahmoodi, Hanaa; Yalda, Mayada; Najeeb, Hishyar (Cellular and Molecular Biology, 2024)
Colorectal cancer (CRC) is the third most frequent type of cancer and the second leading cause of cancer-related deaths globally. Despite a thorough understanding of its biology, etiology, and epidemiology, an estimated 1.8 million new cases are diagnosed each year, and 900000 people die as a result of malignancy. The current study aims to investigate the expression pattern of S100A4 and S100A14 proteins in CRC tissue specimens and a panel of cell lines. Furthermore, to explore the metastatic potential of the aforementioned proteins in relation to the epithelial-mesenchymal transition and their possible association with the clinical features of CRC. The present study involved 80 patients diagnosed with CRC. Upon identification of the sociodemographic and clinicopathological features of the participants, immunohistochemical studies were conducted to measure the expression pattern of the S100 proteins in CRC tissues. In addition to qPCR and western blot studies, a series of in vitro experiments were conducted in a panel of CRC cell lines to assess the effects of S100 protein expression in cell migration, invasion, and proliferation. The number of CRC patients with high S100A4 expression levels was considerably higher than those with low expression (p < 0.0001). S100A4 is positively correlated with TNM staging, nodal metastasis, distant metastasis, and perineural invasion and was statistically significant (p = 0.02, 0.01, 0.0001, and 0.02, respectively). In vitro studies demonstrated that S100A14 knockdown induced EMT and resulted in a substantial increase in cell proliferation, migration, and invasion in HT29 cells. Moreover, S100A4 knockdown substantially inhibited migration, invasion, and proliferation in LoVo cells. The findings collectively suggest that both S100A4 and S100A14 play a pivotal role in colorectal cancer progression. Overexpression of S100A4 consistently with S100A14 downregulation is associated with the activation of epithelial-mesenchymal transition, which in turn enhances cell proliferation, migration, and invasion.